IDENTIFYING COMPETENCIES IN DESIGNING THE EDUCATIONAL PROGRAM «SMART CITY» - Zakirova, Zakirova A.B.; Koshanova , D.K.; Akhayeva, Zh.B (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
Educational program (EP) is a document where the application of an individual approach to students is ensured, so do the transformation of professional competencies from professional standards and qualification standards into learning outcomes. Innovative educational program «7MO1511(2) – Technologies – Smart City» has been developed in order to prepare masters of IT education on the basis of a multidisciplinary approach to allow the students to possess fundamental knowledge and practical skills in the fields of analysis of the development, management and services of the Internet and the use of SMART technology. However, the EP can be successful if the competencies of students are determined. In this article, the main component of educational program is discussed. The competencies were indentified under the professional standards developed by «Atameken». The concepts of competency, professional standard and educational programs are given.